Testimonial Injustice in YouTube Comment Sections: An Epistemological Reflection on Digital Discourse - Syarifah Syarifah; Jumino Suhadi; Devi Pratiwy (Universitas Negeri Gorontalo, 2026)
YouTube comment sections are often treated as noisy and trivial spaces, yet they function as important arenas where people negotiate knowledge, credibility, and authority. This article examines how testimonial injustice unfolds in YouTube comment sections through everyday interactions surrounding contested knowledge claims. Drawing on social epistemology, particularly the concept of testimonial injustice, this study focuses on how speakers are believed, dismissed, or granted authority in digital discourse. Using qualitative discourse analysis, the data consist of selected comment threads responding to a viral YouTube video related to the Apollo moon landing. The comments were drawn from a dataset of 1,264 comments collected between 15 December 2025 and 1 March 2026, from which 9 comments and reply threads were purposively selected for detailed analysis. As YouTube comment sections continue to grow over time, the dataset reflects the comments available during the specified data collection period. The analysis shows four recurring epistemic patterns: credibility deficit, where testimonies are dismissed without engagement; uptake failure, where attempts to explain or correct information receive partial or no epistemic recognition; identity-based credibility judgments, where speakers are evaluated based on perceived competence rather than the content of their claims; and credibility excess, where confidence and technical tone grant undue epistemic authority. These findings suggest that YouTube comment sections are not merely spaces of misinformation or disagreement, but sites where epistemic norms are actively negotiated and often unevenly distributed. This article contributes to digital discourse studies by highlighting how testimonial injustice operates in everyday online interactions and by positioning YouTube as an epistemically consequential space rather than a marginal one.